Multivariate Model for Forecasting the Wheat Prices in India - Karjagi, Rajashekhar; Chakrabarty, Chiragra; Mohite, Raosaheb (Indian Journal of Marketing, 2010)
The present study attempts to develop an econometric model for both long-term and short-term forecasting of wheat prices in India. The detailed methodology involved in developing the model and forecasting process can be understood in this paper. The short-term forecasting was studied by using lagged response model, whereas, the long-term forecasting was made with the help of a multivariate model.